A body of work, a missed opportunity: Dyadic research in older adults. Issue 4 (11th January 2019) - Buck, Harleah G.; Bekelman, David; Cameron, Jan; Chung, Misook; Hooker, Stephanie; Pucciarelli, Gianluca; Stromberg, Anna; Riegel, Barbara; Vellone, Ercole
Abstract : See the Reply byRiffin et al .